Microbial inoculants for enhancing degradation of biosolid waste in aerobic composting - Shilpa, P (Department of Agricultural Microbiology College of Horticulture, 2019)
Solid waste management is a major challenge throughout the world, especially in urban areas, due to the rapid growth of population along with urbanization. Earlier, centralized management of biosolid waste was being practiced. However, due to problems in transportation and segregation, management at source is being promoted. Aerobic composting has been practiced from time immemorial for recycling of biosolid waste, using various processes and containers. Recently, more importance is being given to bio- composting, considering the efficiency of microorganisms in enhancing degradation of organic substrates by their multiple mode of action. Hence, this study was taken up to explore microorganisms which can enhance the process of aerobic composting of biosolid waste. Isolation of potential decomposing microorganisms was attempted from different compost samples including coir pith compost, kitchen waste compost and Oushadhi ayurvedic compost. A total of 14 isolates were obtained from different compost samples. All the isolates were assigned names depending upon the type of microorganism and the source from which they were isolated. Based on the ability to degrade the chemical components in selective medium, four isolates (BaBc-1, BaCp-1, BaOu-1 and AcOu-1) and four reference cultures (Bacillus subtilis, Bacillus niabensis, Gongronella butleri and Trichoderma asperellum) were selected for quantitative assay. Enzyme assay was carried out for selected isolates and the isolate G. butleri exhibited highest cellulase activity. BaBc-1, B. subtilis and BaOu-1 recorded significantly higher β- 1, 3 glucanase activity. Glucosidase activity was found to be significantly high in G. butleri, T. asperellum, BaBc-1 and B. subtilis. Significantly higher laccase, amylase and pectinase activity was recorded in BaOu-1, BaBc-1 and AcOu-1 respectively. Maximum protease activity was recorded in fungal isolates G. butleri and T. asperellum. Potential isolates were further subjected to cultural, morphological, biochemical and molecular characterization. The isolate BaBc-1 showed maximum homology to Bacillus subtilis, BaCp-1 to Bacillus cereus, BaOu-1 to Bacillus sp. and the actinomycete isolate AcOu-1 to Streptomyces roseofulvus. The compatible combinations of selected isolates with high enzyme activity were selected for formulation of microbial consortia and the consortia were evaluated for degrading vegetable waste under in vitro condition. All the inoculated treatments showed faster degradation compared to uninoculated control. Based on visual observations, per cent weight reduction, enzyme activity and microbial population on 21 DAI in flask culture, consortium II (B. subtilis BaBc-1+ T.asperellum+ Bacillus sp. BaOu-1) and consortium IV (B. subtilis+ G. butleri +B. subtilis BaBc-1) were selected for pilot scale experiment. The efficiency of selected consortia was evaluated in KAU smart biobin along with cow dung slurry and uninoculated treatment. In T1 (B. subtilis BaBc-1+ T.asperellum+ Bacillus sp. BaOu-1) compost formation was initiated within 17 days after inoculation. Based on the volume reduction, duration of composting process, yield of compost, microbial population and phytotoxicity of compost, consortium I (B. subtilis BaBc-1+ T.asperellum+ Bacillus sp. BaOu-1) was selected as best performing consortium in KAU smart biobin. Hence, this consortial formulation was selected for large scale experiment in Thumburmuzhi composting units. Cow dung was used as inoculum in positive control and uninoculated treatment served as negative control. The treatment T1 (B. subtilis BaBc-1+ T.asperellum+ Bacillus sp. BaOu-1) recorded maximum temperature (640C) during composting period, faster volume reduction and maximum microbial population in compost. Based on these results, T1 was found to be the best treatment in Thumburmuzhi composting unit. The study revealed that, consortial formulation of B. subtilis BaBc-1, T. asperellum and Bacillus sp. BaOu-1 could be exploited for enhancing degradation of biosolid waste in aerobic composting. This can be used in future for the management of agricultural and municipal solid waste. The plant growth promoting (PGP) activities of these isolates could be an added advantage in improving the growth and yield of plants.